Tinjauan Pustaka Sistematis: Kreativitas Pembelajaran Matematika - Syifa Yuliati; Worowirastri Ekowati, Dyah; Jantung Amelia, Delora; Sumarsono, Puji; Rahmawati Atitik, Agustinah (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
Creativity has a vital role in mathematics learning; this has attracted the attention of researchers, thereby increasing publications related to student creativity in mathematics learning. This research aims to describe the trends and contributions of creativity research in Scopus-indexed journals and their opportunities in the future. This research conducted a Systematic Literature Review (SLR), which summarizes research trends and participation related to mathematical creativity published in Scopus-indexed journals. A search was conducted using the keywords "creativity," "mathematics," and "learning," which resulted in 321 articles. Of these, 21 articles were eligible for analysis. The method used is the review and meta-analysis method (PRISMA). Research on creativity in mathematics learning will increase in 2020-2022, predominantly using a Mix-method approach. Practical implications include assessing student creativity based on fluency, flexibility, and novelty. The results of these findings can be used as a reference or starting point for researchers to evaluate the theme of creativity in mathematics learning according to their individual goals.